La difusión histórica y la recuperación de la memoria: una reflexión introspectiva a partir del proyecto clionet de costa rica - Marín Hernández, Juan José (Revista de historia., 2003)
This work intends to circumscribe the concepts on diffusion, dissemination, applied history, and the extension of history, in line with the historiographical practices of the past 30 years. The author underscores the need to create history with the people under the philosophy of action-research, as an essential part of the dissemination of history. In the end, the article presents the example of how the Clionet Costa Rica Project has tried to link the scope of investigation, teaching, and extension through the use of new technologies.